Polar constituents of oils and bitumens – new applications to Petroleum Geochemistry and (Palaeo)Biogeochemistry - Hallmann, Christian Olivier Eduard (Curtin University, 2008)
Polar organic molecules are defined by differences in electronegativity between their atomic constituents and the resulting asymmetrical structures. They represent the basic chemical building blocks of life. Having a strong affinity to water (H[subscript]2O), which is essential for life on Earth, polar molecules are studied by the discipline of biochemistry and their origin, distribution, and function in living systems is relatively well understood. Polar constituents of sedimentary organic matter and petroleum have been previously studied but they are, in general, yet far from being understood. They can be present as primary biogenic molecules, rearranged biogenic molecules, or secondary functionalized hydrocarbons. The studies compiled in this thesis use selected polar organic compounds as molecular tools: phospholipids as indicators of biomass, high-molecular-weight polycyclic aromatic hydrocarbons as combustion markers, phenols as indicators of oil-water interaction processes, and carboxylic acids in general.Chapter 2 studies the biological oxidation of petroleum accumulations; a process mediated by microbes that inhabit the deep subsurface and affect the long-term storage of living carbon as sedimentary biomass of the ‘deep biosphere’. The results presented in chapter 2 suggest that intact bacterial cells are present in biodegraded petroleum, as indicated by the detection of membrane lipid fragments, termed phospholipids, in these oil samples. Carboxylic acids released from phospholipids (i.e. phospholipid fatty acids, PLFA) in oil samples vary in concentration (~2.0 - ~10.0 µg/g oil) and composition (i-C[subscript]14:0 dominated vs. i-C[subscript]15:0 and i-C[subscript]17:0 dominated) during progressive petroleum biodegradation, thereby showing that the microbial community increases in size during the removal of petroleum constituents, and that the community structure changes. Not one but at least two structurally different microbial consortia are shown to be responsible for petroleum degradation. Chapter 4 evaluates the rapid oxidation of biomass during the impact of an extraterrestrial bolide, which occurred during the late Neoproterozoic.The co-occurrence of a -3.5‰ negative sedimentary stable carbon isotope excursion and a molecular combustion-marker anomaly (coronene; 0.48 ppb, relative to a 0.04 ppb background), which are followed by a diversification of Acritarch species, suggests that combustion of ‘early’ terrestrial and marginallymarine biomass might have caused extensive smoke and atmospheric dimming, as well as subsequent photosynthetic stress. Moreover, the sharp combustion marker anomaly can probably provide a long-sought chronostratigraphic marker for the late Neoproterozoic, when also detected in other locations around the globe. Chapter 5 evaluates the effects of petroleum interaction with water. For this purpose oils produced from one reservoir were monitored during a 335-day period following the rationale that oil-water interaction increases during petroleum production. Based on a selective depletion of volatile aromatics and invariant phenol concentrations the results exclude both evaporative and oil-water partitioning processes. Petroleum compositional changes, recorded mainly in the low-molecular-weight aromatic and phenol fractions, were tentatively attributed to abiotic oxidation processes. Furthermore, methodological advances in the analysis of carboxylic acids of low molecular weight, evaluated for the execution of the other studies, are presented in chapter 4.Overall, the presented results shed more light on carbon export fluxes from different sedimentary carbon reservoirs by shedding new light on deep biosphere metabolism, elucidating the significance of the Neoproterozoic Acraman impact event, and contributing to our knowledge of petroleum destruction through its interaction with water in sedimentary basins. Moreover, they show that, in contrast to traditional belief, NSO compounds in oils and bitumens can form useful molecular tools to study questions in petroleum geochemistry, biogeochemistry, and palaeobiogeochemistry. Understanding the size of carbon reservoirs and fluxes on Earth, as well as the mechanisms that cause these carbon fluxes, can increase our appreciation of global biogeochemical cycling and, in turn, explain ecosystem dynamics, past evolutionary events, and predict future change of current climatic conditions.